Study of the influence of temperature the venting depollution process of soils contaminated with volatile organic compounds - GABRIELA-ALINA BRUSTUREAN (Journal of the Serbian Chemical Society, 2006)
Venting is one of the most used in situ remediation methods for unsaturated soils contaiminated with volatile organic compounds (VOC). The development of mathematical models and their validation by means of experimental results allowed the identification of the main parameters which influence the soil depollution process. The influence of temperature on the venting depollution process of soils polluted with volatile organic compounds was studied in this investigation. It was found that the depollution efficiency is strongly influenced by the vapour pressuree of the pollutants. The conclusions, derived from the performed experimental determinations allowed characterization of the depollution process by using an "equilibrium" model. This model considers the existence of equilibrium between the four pollution phases (vapour, aqueous, "solid" and non-aqueous phase organic liquids) at any moment in time. In order to calculate the vapour pressure, a modified equation of the Antoine model was used in the model. Application of the mathematical model indicates that a 10 °C temperature rise leads to a two-fold increase in the vapor pressure of a compound. Comparison of the modeled and experimental curves, as well as the values of the obtained performance critterions, verified that the chosen mathematical model describes the influence of temperature on the depollution process very well.